How Past Work Stressors Influence Psychological Well-Being in the Face of Current Adversity: Affective Reactivity to Adversity as an Explanatory Mechanism - Miriam Schilbach; Anja Baethge; Thomas Rigotti (Journal of Business and Psychology, 2023)
This study advances the understanding of the mechanisms that link past challenge and hindrance stressors to resilience outcomes, as indicated by emotional and psychosomatic strain in the face of current adversity. Building on the propositions of Conservation of Resources Theory and applying them to the challenge-hindrance framework, we argue that challenge and hindrance stressors experienced in the past relate to different patterns of affective reactivity to current adversity, which in turn predict resilience outcomes. To test these assumptions, we collected data from 134 employees who provided information on work stressors between April 2018 and November 2019 (T0). During the first COVID-19 lockdown (March/April 2020), the same individuals participated in a weekly study over the course of 6 weeks (T1–T6). To test our assumptions, we combined the pre- and peri-pandemic data. We first conducted multilevel random slope analyses and extracted individual slopes indicating affective reactivity to COVID-19 adversity in positive and negative affect. Next, results of path analyses showed that past challenge stressors were associated with lower affective reactivity to COVID-19 adversity in positive affect, and in turn with lower levels of emotional and psychosomatic strain. Past hindrance stressors were associated with greater affective reactivity to COVID-19 adversity in positive and negative affect, and in turn to higher strain. Taken together, our study outlines that past work stressors may differentially affect employees' reactivity and resilient outcomes in the face of current nonwork adversity. These spillover effects highlight the central role of work stressors in shaping employee resilience across contexts and domains.
Keywords: 650; Resilience; Affective reactivity; Conservation of Resources Theory; Challenge-hindrance framework